Acknowledgements and Guidelines - Shahab, Aisyah (Politeknik Negeri Sriwijaya, 2022)
extend their gratitude and appreciation to the reviewers for their scrupulous work in reading and reviewing the articles, and offering remarks and corrections for the betterment of the present issue. However, any possible deficiency and negligence are the responsibility of the Journal Management.